A Study on QTc Prolongation as An Indicator of Cardiac Autonomic Neuropathy in Diabetic Patients at Bir Hospital, Nepal - Yadav, Shree Narayan Yadav; Mani Prasad Gautam; Adhikari, Pushpa; Koirala, Sunil Ram; Yadav, Duryodhan (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Diabetes mellitus frequently leads to cardiac autonomic neuropathy (CAN), a complication that disrupts heart rate control and vascular function, increasing the risk of silent myocardial ischemia and sudden cardiac death. Prolonged QTc interval on ECG has emerged as a reliable marker for detecting CAN. Methods: A cross-sectional study was conducted on 100 diabetic patients at NAMS, Bir Hospital, Nepal, from September 2021 to June 2022. Data on QTc intervals and other clinical parameters were analyzed using STATA 13.0 software. Results: Among the 100 patients, 60% were diagnosed with CAN. Of these, 20% had severe CAN and 40% had early-stage CAN. Patients with severe CAN had a longer duration of diabetes and higher blood sugar levels compared to those without CAN. QTc interval was significantly prolonged in 58% of patients with CAN, indicating a strong correlation between QTc prolongation and CAN severity. Conclusion: QTc interval prolongation is closely associated with the severity of CAN, making it a practical and efficient tool for early detection in diabetic patients. Recognizing prolonged QTc can help identify patients at higher risk of sudden cardiac death, emphasizing the need for further large-scale studies.